Effectiveness of a Staff Promoted Wellness Program to Improve Health in Residents of a Mental Health Long-Term Care Facility. (2nd April 2016) - Hutchison, Shari L.; Terhorst, Lauren; Murtaugh, Stephanie; Gross, Sarah; Kogan, Jane N.; Shaffer, Sherry L.
Abstract : The current study describes physical and mental health outcomes during a health promotion program for individuals with serious mental illness (SMI). A sample of 43 adults in a long-term residential facility volunteered for an individualized, healthy lifestyle program designed to promote physical activity and combat premature mortality among individuals with SMI. Nurses and residential counselors were trained in the program and encouraged to work collaboratively with the program's personal trainers. Weekly nutrition and activity logs were obtained over the year-long evaluation. Assessments of physical and psychological health indicators were collected quarterly. Qualitative data through focus groups described staff experience. Self-report of moderate and vigorous physical activity improved over time as did fitness level as measured through a walking challenge ( p = .001). Significant decreases in weight ( p < .001), BMI ( p = .001), and total cholesterol ( p < .001) were observed from baseline through 12 months. Mean recovery scores (RMQ) were significantly higher between baseline and all time points ( p < .001). Participants reported decreasing levels of depression (PHQ-9) by the 12-month time point ( p < .001). Staff encouraged participation in physical activity and observed improved motivation and socialization among participants. A health promotion program with participation encouraged by health care staff is effective for increasing physical activity and improving physical and mental health outcomes in individuals with SMI in long-term residential care.